Factors Associated with the Incidence of Diabetic Ulcers in Clients with Diabetes Mellitus at Labuang Baji Hospital Makassar - Nusdin, Nusdin; Awaluddin, Achmad Indra (Alta Dharma Publisher, 2023)
Background: Diabetes Mellitus is classified into a group of metabolic diseases with specific characteristics of increased blood sugar levels or hyperglycemia. Clients with Diabetes Mellitus have the potential for 15-25% to experience diabetic foot ulcers caused by the factors of cholesterol, use of footwear, and self-management of diabetes mellitus. Objectives: This study aims to determine factors associated with the incidence of diabetic ulcers in clients with diabetes mellitus at Labuang Baji Hospital Makassar. Methods: The type of research used was quantitative with a cross-sectional design. The number of samples used was 50 respondents by using accidental sampling. The research instrument used a questionnaires and Standard Operating Procedures for cholesterol examination. Result: The study results using the Spearman Correlation Testshowed a relationship between cholesterol and the incidence of diabetic ulcers in clients with Diabetes Mellitus with the p-value = 0.001 (p <0.05). There is a relationship between footwear usage and the incidence of diabetic ulcers in clients with diabetes mellitus with the p-value = 0.001 (p < 0.05) and there is a relationship between Self Management Diabetes Mellitus (SMDM) with the incidence of diabetic ulcers in clients with diabetes mellitus with p-value = 0.001 (p<0.05). Conclusion: Cholesterol, footwear usage, and Diabetes Mellitus Self Management (SMDM) are the factors of Diabetic ulcers in clients with diabetes mellitus. Recommendation: This study could be an adjunct for further systemic review and expected for further study to research about the other factor or the effect of treatment sequacity on diabetic ulcer recovery